Prenatal Dietary Exposures and Offspring Body Size from 6 Months to 18 Years: A Systematic Review (P11-019-19). (13th June 2019) - Litvak, Jacqueline; Parekh, Niyati; Deierlein, Andrea
Abstract: Objectives: In utero dietary exposures may influence childhood obesity. Current research on the relationship between prenatal food and beverage intakes and offspring obesity has yielded mixed results. The purpose of this review is to evaluate the relationship between prenatal dietary exposures and offspring body size from 6 months to 18 years. Methods: A systematic review of English articles using PubMed and Web of Science (January 2010- March 2018) was conducted using the PRISMA guidelines. Additional studies were identified through a reference review of articles that met the inclusion criteria and related review articles. Longitudinal observational studies that assessed dietary patterns, food(s) and/or macronutrients(s), or beverage(s) consumption during healthy pregnancy and evaluated offspring body size between the ages of 6 months and 18 years were included in the review. Results: Twenty studies evaluating dietary patterns (n = 6), macronutrient(s) and/or food(s) (n = 11), and beverages (n = 3) met inclusion criteria. Consumption of a Mediterranean dietary pattern during pregnancy was associated with lower anthropometric measures in offspring, while sugars and refined carbohydrates were associated with offspring obesity. Mixed results were observed for n-3 polyunsaturated fatty acids, protein, sugar-sweetened beverages, and artificially sweetened beverages. Conclusions: These findings suggest that following a Mediterranean diet and limiting sugar intake during pregnancy may make small but significant contributions to preventing childhood overweight and obesity. Future research should focus on prenatal diet quality to better communicate the information to health practitioners. Funding Sources: None.